Políticas de inserção de tecnologias digitais como instrumento de reforma na rede estadual de ensino de Goiás (2007-2017) - Echalar, Jhonny David (2021)
This research had as its object of study the analysis and understanding of the relationship between the activities of formulation and implementation of public policies, from the organizational proposal of the Public Policy Cycle, considering the convergence between three elements: the institutional architecture of the Secretariat of State of Education of Goiás (Seduc-GO), the institutional plans of different units and regional administrative spheres and the actions formulated and implemented in Goiás, based on the National Program for Continuing Education in Educational Technology – Integrated ProInfo, 2007. The construction -configuration of the object, in turn, required the historical delineation of the policies for the insertion of Information and Communication Technologies (ICT) by Seduc-GO between 2007 and 2017. These are the elements that inspire the following research problem: how between 2007 and 2017, public policies for the insertion of TDIC were created and implemented by the State Department of Education of Goiás? Methodologically, the research was planned under a qualitative perspective, with exploratory research, using document analysis and semi-structured interviews with managers working in the administrative units of Seduc-GO as a data collection instrument. It is observed, over the time frame, changes both in the institutional architecture and in the plans and actions carried out by that institution, which are not restricted to administrative and organizational issues, but are directly related to a larger, global movement by in other words, the transformation of public policies based on the neoliberal doctrine, a movement materialized, in Goiás, by the reformist policy “Pact for Education”. It is possible to observe the dismantling of a political-administrative structure articulated in a network, previously aimed at continuing education, physical structuring and support for didactic-pedagogical projects. Another point noted is the outsourcing to private organizations of both the continuing education of education professionals and the offer of digital educational resources on their platforms. There is also centrality, by Seduc-GO, in the formulation and implementation of digital systems aimed at pedagogical and administrative management in school units, in a manufacturing perspective in which teachers and managers must nurture such programs linked to a meritocratic policy of bonuses and evaluation of the " school performance". Furthermore, activities for the formulation and implementation of projects aimed only at equipping school units, with low-use artifacts or for the maintenance of the aforementioned business-managerial policies are identified, without the inclusion of elements intrinsic to educational intentions that enable the reduction of inequalities and problems observed in our society.